Factors Affecting the Selling Price of Eel Fish (Anguilla marmorata) in Nokilalaki District, Sigi Regency, Central Sulawesi - Wahid, Abd.; Amiluddin, Amiluddin; Bestari, Andi Nurul Khasanah (Hasanuddin University, 2020)
Eel fish are traded until they are exported to foreign countries such as Japan. This research was conducted during October-November 2019 in Sopu Village Nokilalaki District Sigi Regency Central Sulawesi. The purpose of this study was to determine the production and income of Eel Fish and to analyze the marketing price and the factors that influence the marketing price of Eel Fish in Nokilalaki District Sigi Regency Central Sulawesi. The method used is a combination of qualitative and quantitative methods using the income formula and multiple linear regression formula. The results of this study are, the production of Eel Fish in October 2019 was 93 fish. The income from selling Eel Fish ranges from nominal Rp.600,000 to Rp. 2,500,000 per month. There are several factors that influence the marketing price of eel Fish they are, production costs, number of fish sold, distance of sales location, number of consumers, competitors, and basic income. There is a significant influence of the dependent variable (Marketing Price) with the independent variable (the six factors that influence). The significant influence percentage was 55.1% with the intertwined relationship seen from the value of R approaching 1 which was 0.742. Of all the factors, only the number of consumers (X4) significantly affected the marketing price of Eel Fish in Sopu Village Nokilallaki District Sigi Regency Central Sulawesi.